2014
DOI: 10.1097/01.epx.0000456621.42258.79
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia among community dwelling elderly in Alexandria, Egypt

Abstract: Insomnia is a common problem among the elderly in Alexandria. Female sex, chronic diseases, mental health problems, and bad sleep hygiene practice increase the risk for insomnia. Improving knowledge among the elderly about the prevalence and risk factors of insomnia could help the development of effective public health prevention and intervention programs for better sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
2
14
2
1
Order By: Relevance
“…This finding is contrary with the study conducted in Egypt which reported that being female was the factor associated with insomnia among elderly [15]. Contradictory findings between these studies may be related to small sample size in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is contrary with the study conducted in Egypt which reported that being female was the factor associated with insomnia among elderly [15]. Contradictory findings between these studies may be related to small sample size in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is similar with the findings of the study conducted in Egypt which revealed that physical health problem i.e. pain [13] and nocturia [13,15] were the factors associated with insomnia. Similar findings were revealed in this study too because as people age, they are more likely to develop more than one long-term health problems like chronic pain, nocturia, cough etc.…”
Section: Discussionsupporting
confidence: 91%
“…This was inconsistent with the study conducted in Egypt which reported a range of physical symptoms such as nocturia, restless leg, acidity, heartburn and sleep apnoea results frequent awakenings at night. Furthermore, this range of physical symptoms has more risk for insomnia among all age groups and significantly increased with age (Ayoub, Attia, Kady, & Ashour, ). And also, Bakr, Ezz, Abd Elaziz, Khater, and Fahim () concluded that insomnia is caused by a multitude of health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in insomnia in the aged population cannot be ignored as insomnia is generally higher in women . In older women, with or without symptoms of depression, sleep disturbances increase with age .…”
Section: Insomnia In the Elderlymentioning
confidence: 99%
“…Also, the variation cannot be attributed purely to differences between ethnic groups, rural and non-rural population, and nursing home and non-nursing home data. A relatively low percentage (15%) of elders has insomnia in the Domkhar valley in India's Ladakh Foley et al 55 23-34% USA Ohayon 56 30% France Maggi et al 57 45% Italy Chiu et al 58 38.2% Hong Kong (Chinese population) Babar et al 59 32.6% Hawaii (Japanese Americans) Kim et al 60 26.4% Japan Pallesen et al 61 38.6% Norway Schubert et al 62 26.4% USA Sukying et al 63 46.3% Thailand Su et al 64 6% Taiwan Yu et al 65 10.4% China Bonanni et al 66 44.2% Italy López-Torres et al 67 36.1% Spain Kim et al 68 29.2% South Korea Li et al 69 49.7% China (rural) Tsou 70 41% Taiwan Ayoub et al 71 33.4% Egypt Ford et al 72 21.3% USA Sagayadevan et al 73 13.7% Singapore (Chinese, Malay, Indian descent) Sakamoto et al 74 15.2% Ladakh, India El-Gilany et al 75 62.1% Egypt (rural) Eser et al 76 60.9% Turkey (nursing home) Makhlouf et al 77 33.4% Egypt (geriatric home) Gambhir et al 78 32% India (hospital) Ogunbode et al 80 27.5% Nigeria (geriatric centre) region, which is at a high altitude of 2900-4200 m. 74 According to some reports, there is a higher prevalence of insomnia in the aged in nursing homes and rural areas. 69,75,76 However, other studies have found no differences in the insomnia patterns of elders in nursing homes and in other homes.…”
Section: Insomnia In the Elderlymentioning
confidence: 99%